Henry's box: ladybird picture stories - Roddie, Shen; King, Sue (Ladybird Loughborough, 1998)
Mum gave Henry a box in which to put all those old, unwanted things from his bedroom. A boat with no sail, a tractor without wheels and a bare-chested teddy. But just as the box was full to bursting point, Henry found something to change all that